Еволуција во згрижувањето, прогнозата и квалитетот на живот на пациентите со Хочкинов лимфом - Амзаи, Газменд (Медицински факултет, УКИМ, Скопје, 2018)
Efficient polychemotherapy, precisely focused and optimally dosed radiotherapy, immunotherapy, transplantation, improvement of the staging procedures, significant improvements in supportive measures during myelosuppression, infections and other complications, have contributed to the cure of most of the patients with HL (75-90%), and the effect of the treatment is in correlation with the clinical stage and other prognostic factors of the disease. At our institution we follow and implement into practice these positive trends in the evolution and progress achieved in the process of diagnosing, treatment, and the overall management of patients with Hodgkin disease, which is reflected in the overall surival of our analyzed patient population, reaching 83.5% at 10 years. The present study is designed as a retrospective-prospective one, and it includes 287 patients with Hodgkin's lymphoma, diagnosed and treated at the University Clinic for Hematology in Skopje, in the period from 2005 until 2015. The patients are above the age of 14, with a documented histopathological diagnosis of Hodgkin's lymphoma and with valid medical documentation, including clinical and laboratory data on their initial condition, the administered therapy, as well as the clinical follow-up of the patients. An analysis of the spermogram, performing an ECG, echocardiography and spirometric examinations are warranted for detection of potential late complications, resulting from the treatment of patients, following long-term remissions. The basic clinical features of the analyzed population correlate with those reported in the relevant medical literature, with slight deviations. Most of the de novo diagnosed patients (91.6%) are treated with ABVD chemotherapy as a frontline choice. Optimal response to treatment, i.e. remission, is achieved by 88.4% of the treated patients. Nevertheless, 9.8% of the patients remain primarily refractory to treatment, whereas one or more relapses following CR, have been noted in 16% of the patients. The analysis of the results regarding the treatment of R/R HL patients, using various therapeutic approaches, defines BEACOPP as the most efficient option. High-dose chemotherapy, followed by autologous hematopoietic stem cell graft, as a strategy for our R/R patients, ensures a 5-year overall survival for 51% of the patients, whereas 45% of the patients survive more than 10 years. The International Prognostic Index (IPI) is absolutely applicable to our group of analyzed patients. The influence of many parameters, regarding the overall survival rate, has been analyzed utilizing various statistical methods. The multivariate statistical analysis has distinguished the hemoglobin level and the clinical stage of the disease as prognostically significant regarding the vital statistics. Nonetheless, despite the progress achieved regarding treatment outcomes due to optimization of therapeutic protocols, the issue of potential side effects, arising as a treatment consequence, remains open. These include late adverse consequences, such as the risk of second malignancy (in 8.7% of our treated patients), the risk of non-neoplastic complications, mainly cardiac (20.8%) and pulmonary complications (24.7%), as well as the risk of developing secondary infertility, which is of imperative importance for the patients’ quality of life. ABVD carries a low degree of gonadotoxicity, which is also confirmed in our analyzed patient population treated with ABVD chemotherapy, resulting in low risk for infertility: 6.1% of the men had spermogram irregularities, and 18.9% of the women manifested disruptions in their menstrual cycle, of which 85% were over the age of 30. The sperm of the patients with HL is with poorer quality, compared to the healthy male control population, even prior to treatment, which is confirmed by as high as 15% abnormal findings.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Оливер Каранфилски.